2005
DOI: 10.1002/ejic.200400713
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Complexes of Chelating, Dianionic O,S,O‐Bisphenolato Ligands: Syntheses, Characterisation, and Catalytic Activity

Abstract: Titanium complexes based on 2,2′‐thiobis[4‐(1,1,3,3‐tetramethylbutyl)phenolato] (tbop) are prepared by reaction of TiCl4 or Ti(NMe2)4 with the parent biphenol. Three new complexes are reported: [Ti2(μ‐tbop‐κ3O,S,O)(μ‐tbop‐κ2O,O)‐(tbop‐κ3O,S,O)Cl2] (1)·2 CH3CN, [Ti2(μ‐tbop‐κ3O,S,O)2Cl4] (2) and [Ti(tbop‐κ3O,S,O)2] (3). Substitution of the chlorides in 1 and 2 by 2,6‐diisopropylphenolato and imido (NtBu) ligands generates the new compounds [Ti2(μ‐tbop‐κ3O,S,O)2‐Cl2(dipp)2] (4)·Et2O and [Ti2(μ‐tbop‐κ3O,S,O)2(NtBu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…In contrast to previously reported heteroleptic tbop-Ti catalysts, preliminary polymerization results showed that complexes 1 − 6 when activated with aluminum alkyls were inactive in ethene polymerization. The lack of catalytic activity can explain the fact that formally considered 16-electron complexes 4 − 6 are coordinatively saturated species and there is no vacancy for the incoming olefin.…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…In contrast to previously reported heteroleptic tbop-Ti catalysts, preliminary polymerization results showed that complexes 1 − 6 when activated with aluminum alkyls were inactive in ethene polymerization. The lack of catalytic activity can explain the fact that formally considered 16-electron complexes 4 − 6 are coordinatively saturated species and there is no vacancy for the incoming olefin.…”
Section: Resultscontrasting
confidence: 76%
“…The structures of both complexes reveal eight-coordinate Zr or Hf metal centers with a dodecahedral geometry and tetrahedral aluminum atoms linked via oxygen atoms of the tbop ligands. The M−O distances are very similar in both complexes and as expected significantly longer than those for terminal Zr and Hf aryloxides 2a,d-f,8 Also M−S and M−C bond lengths in both 5 and 6 display similar trends and do not reveal unusual features. 2d,f,g,j,l, The Al−O bond lengths are close to those found in other structures of the aluminum aryloxides. , The Al−C bond lengths are clearly within the range expected for the terminal Al−C bond distances. ,
1 Molecular structure of [M(μ-tbop-κ 3 O,S,O) 2 Me 2 (AlMe 2 ) 2 ] [where M = Zr ( 5 ) or Hf ( 6 )] ( 6 shown, hydrogen atoms omitted for clarity). Selected bond lengths (Å): 5 , Zr−O(1) 2.307(3), Zr−O(2) 2.225(3), Zr−S(1) 2.794(2), Zr−C(1) 2.286(4), Zr−C(2) 2.283(4), Al(1)−O(1) 1.847(3), Al(1)−O(3) 1.856(3), Al(1)−C(3) 1.959(4), Al(1)−C(4) 1.954(4); 6 , Hf−O(1) 2.306(6), Hf−O(2) 2.196(6), Hf−S(1) 2.796(4), Hf−C(1) 2.246(9), Hf−C(2) 2.260(9), Al(1)−O(1) 1.818(7), Al(1)−O(3) 1.886(6), Al(1)−C(3) 1.956(9), Al(1)−C(4) 1.934(9).
…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations